Tathbiq Washilah Aflām al Kartun al Arabiyyah Fi Tarqiyyah Itqān al Mufradāt al Arabiyyah li Tholibāt al Fashl al Tāsi’ Fi al Madrasah al Tsanawiyah “ Al Washoya” Ngoro Jombang - Agustya Putri, Elfira; Mu'at (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2024)
This research is motivated by the lack of mastery of vocabulary among students, and that there are students who feel fear and embarrassment during the process of giving vocabulary and learning the Arabic language because they find it difficult to memorize vocabulary, and the students’ lack of interest in vocabulary when learning the Arabic language process. As for the results of the research, we can be summarized as follows: (1) The method of cartoon films is a simple method, which helps facilitate students’ understanding of the concept of learning so that they can achieve good achievements. Using the medium of cartoons makes students excited and gives greater interest in continuing to learn the Arabic language. (2) Learning is more continuous and productive, can adapt learning time, eliminate the boredom of demands in learning, increase the motivation of demands in learning something or arouse the passion for learning. (3) The factors supporting the application of the cartoon film method are the availability of the cartoon film method that is easy to make, auxiliary devices such as LCD screens, plugs, speakers, laptops, as well as whiteboards or walls. Inhibiting factors There are still students who still have difficulty reading Arabic and this usually happens to students who are not from religious schools but from primary schools so that the ability of students to read Arabic is still lacking.